Hidden Debt Forms of the Local Authorities – an Attempt of Assessment - Mateusz Langer (Prawo Budżetowe Państwa i Samorządu)
The article presents some of the most important issues related to the hidden debt forms of the local authority in Poland. In particular, draws attention to the characteristic of different types of them. Additionally, this article discusses a significant provision of laws, which has provided by the Minister of Finance to elimination of debt limit evasion. Moreover, bearing in mind the above is should be noted that the necessity of consider the non-budgetary funds in the budget reporting.